The Rationality of Drug Use in GERD Patients at The Outpatient Installation of RSUD Dr. Soedarso Pontianak - Yuswar, Muhammad Akib; Aisiyah, Nurul; Purwanti, Nera Umilia (Jurnal Kesehatan, 2023)
Gastroesophageal Reflux Disease (GERD) prevalence has increased from 2016 to 2018 by 21,6%. Inappropriate indication, drug, dose, route of administration, and time interval of administration could lead to therapeutic failure. This study aimed to evaluate the rationality of drug use and the distribution of drug use patterns in GERD patients at the outpatient installation of RSUD Dr. Soedarso Pontianak. This research method is descriptive and observational with a cross-sectional design. Data collection was delivered retrospectively with medical records data and prescriptions of GERD patients during the 2020-2021 period. The sampling technique used is purposive sampling, where the sample selection is based on the specified inclusion criteria. The sample used in the study was 98 patients. The results showed that the percentage of rationality in patients without comorbidities was based on 100% correct indication, 93,85% correct drug, 100% correct dose, 100% valid route of administration, and 100% accurate time interval for administration and with comorbidities based on proper indication 87,88%, 57,58% correct drug, 100% correct dose, 100% correct route of administration, and 100% accurate time interval for administration. Distribution pattern of GERD drug use in GERD patients without/with comorbidities was the most widely used is Lansoprazole (monotherapy). The most commonly used is a Proton Pump Inhibitor (PPI) with sucralfate for the benefit of combination drugs.